Enhancing Computer Science Education Through Electronic Team-Based Learning: A Hybrid Approach to Collaborative Learning - Makalew, Brilly Andro; Pardamean, Bens (Bina Nusantara University, 2024)
This paper explores the implementation of electronic Team-Based Learning (e-TBL) as a hybrid educational solution, combining traditional TBL methodologies with electronic platforms to enhance collaborative learning experiences. The study aims to assess the effectiveness of e-TBL in improving knowledge acquisition, teamwork skills, and overall academic performance among computer science students. The research was conducted in five phases, including preparation, experimentation, and evaluation, with a focus on developing an e-learning application integrated with Moodle. The results indicated significant improvements in student motivation, engagement, and academic achievement. The study concludes with recommendations for integrating e-TBL in various educational settings, highlighting its adaptability and potential for enhancing learning outcomes in both traditional and online environments.